Outcomes of kidney transplants and risk of infection transmission from increased infectious risk donors. Issue 8 (27th June 2016) - Limkemann, Ashley J.; Wolfe, Luke; Sharma, Amit; King, Anne L.; Behnke, Martha; Shah, Mili Jay; Posner, Marc P.; Cotterell, Adrian H.; Bhati, Chandra S.; Gupta, Ankur; Kumar, Dhiren; Gupta, Gaurav
Abstract: Concern over transmission of viral infections has been reported to result in higher discard rates of high infectious risk kidneys (HIR) although data on actual viral transmission rates are lacking. At our center, we performed 89 HIR and 533 non‐HIR kidney transplants (KTs) between 2004 and 2011. Follow‐up screening labs in recipients of HIR kidneys tested for human immunodeficiency virus, hepatitis C virus, and hepatitis B virus did not reveal any cases of viral transmission over median follow‐up of 4.3 years. Patient and graft outcomes were similar at 5 years between HIR and non‐HIR KTs. An updated analysis of the Organ Procurement and Transplant Network (OPTN) registry of deceased‐donor kidney transplants between 2008 and 2012 included 57 526 transplants was performed. Retrospective calculation of KDRI (kidney donor risk index) differed ( P <.001) between all groups with median KDRI of 0.99 for HIR kidneys, 1.07 for non‐HIR standard criteria donor kidneys, and 1.81 for non‐HIR expanded criteria donor (ECD) kidneys. This was reflected in the significantly improved 5‐year graft survival for HIR KTs when compared with non‐HIR ECD KTs (84% vs 78%; P <.001). Our data can guide counseling of KT candidates about the safety and benefits of HIR kidneys.